2012
DOI: 10.1002/cjce.21738
|View full text |Cite
|
Sign up to set email alerts
|

Common vulnerabilities of RTO implementations in real chemical processes

Abstract: Real‐time optimisation (RTO) systems face challenging scenarios in industrial practice, such as incomplete and corrupted process information, uncertain large‐scale mathematical models and numerical optimisation issues. Proper design of RTO structure and robust diagnosis tools are keys for good performance, although they are neglected in commercial RTO software and not fully solved in the technical literature. This article reviews the concepts behind the two‐step RTO approach and suggests performance metrics. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Quelhas et al [66], however, brought attention to the fact that the estimation problem must be carefully designed. Dealing with a two-step RTO applied to an industrial ethylene production plant, it is shown that the typical trajectories of the estimated heat transfer coefficients indicate that some of the model parameters are not estimable when the parameter estimation is performed independently and simultaneously with the data reconciliation procedure, which might be due to correlation with other parameters and process data or because they do not affect the objection function significantly.…”
Section: Solution Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quelhas et al [66], however, brought attention to the fact that the estimation problem must be carefully designed. Dealing with a two-step RTO applied to an industrial ethylene production plant, it is shown that the typical trajectories of the estimated heat transfer coefficients indicate that some of the model parameters are not estimable when the parameter estimation is performed independently and simultaneously with the data reconciliation procedure, which might be due to correlation with other parameters and process data or because they do not affect the objection function significantly.…”
Section: Solution Strategiesmentioning
confidence: 99%
“…Nevertheless, they should be analyzed during the design of a DR application trying to answer whether the optimization problem is being satisfactory solved. Although DR generates benefits, it can have strong negative effects when some hypothesis is violated or the procedure does not find a feasible solution, and using reconciled data could yield worse results than using the measurements directly [65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…• The success rate of modern convex solvers is much higher than that of SQP solvers and can virtually reach 100%, 32 which is a very nice feature for industrial RTO applications 8 .…”
Section: Advantages Of Convex Modelsmentioning
confidence: 99%
“…There are still a significant number of difficulties that limit the wide application of RTO in industry 8,9 . The main limitation is without any doubt the inability of the RTO schemes to find the plant optimum in the presence of structural plant-model mismatch 5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, plant-model mismatch is not the only vulnerability of RTO systems, whose performance can also be jeopardized by incomplete and corrupted process information, absence of knowledge regarding measurement errors and performance issues related to numerical optimization techniques [31]. In addition, the use of continuous system diagnostic tools is not common, neither in the literature, nor in commercial RTO systems.…”
Section: Introductionmentioning
confidence: 99%